Why innovation depends on intellectual honesty : fostering psychological safety isn't enough if managers don't pay particular attention to creating conditions for healthy debate - Dyer, Jeff (Professor of strategy); Furr, Nathan R.; Lefrandt, Curtis T.; Howell, Taeya (MIT Sloan Management Review, 2023)
Fostering psychological safety isn’t enough to succeed at innovation if managers don’t pay particular attention to creating conditions for healthy debate. If leaders can balance psychological safety with open, honest debate, they gain the benefits of both. The authors describe the factors most important to establishing this balance and outline what leaders can do to create a high-performance learning and innovation culture.